Product Influence Matrix on Purchase Intentions: Unravelling the Dynamics of Consumer Perception Towards Smartphone - Shrestha, Sajeeb (MultiTech Publisher, 2024)
This research study aims to examine consumer perceptions regarding the product influence matrix and its impact on purchase intentions among smartphone users in the Kathmandu Valley of Nepal. A descriptive and exploratory research design was employed, and data was collected through questionnaires distributed both in-person and online. The sample size of 412 respondents was determined using non-probability convenience sampling. The results showed that compatibility, brand, product features, and social influence were positively perceived by consumers, with compatibility and brand being the most influential factors. However, purchase intention received a slightly lower mean score, suggesting that there might be other factors influencing consumers' purchase decisions. The correlation analysis revealed significant correlations between all the product influence factors and purchase intention. The multiple regression analysis demonstrated that the combination of compatibility, brand, product features, and social influence significantly predicted purchase intention, explaining approximately 65.4% of its variance. The findings suggest that building strong brands, emphasizing attractive product features, and leveraging social influence can positively impact consumers' purchase intentions. The study provides valuable insights for smartphone marketers in understanding and influencing consumer behaviour in the Kathmandu Valley market. However, further research is recommended to explore specific aspects of compatibility and identify additional factors that may influence consumer purchasing decisions in this context.